2017
DOI: 10.1038/s41598-017-17060-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of soil C:N ratio and δ13C in wheat-maize cropping system of the North China Plain and influences of the Yellow River

Abstract: To better understand the characteristics of soil organic matter (SOM) in the North China Plain, we evaluate the large scale variations of soil organic carbon (SOC), total nitrogen (TN), carbon to nitrogen (C:N) ratio and stable carbon isotopic compositions (δ13C) in SOC over 0–100 cm. To assess the influence of the Yellow River, 31 sites are selected from the wheat-maize double cropping system, and grouped into two: 10 sites near and 21 sites far from the river. Our data show that mean soil C:N ratio is low (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Recent studies have revealed that in the YRD, SOC stock is generally lower in the higher salinity soils (3.05 kg C m −2 in the 0–60 cm) (Setia et al, 2013) than in the lower salinity soils (5.73 kg C m −2 in the 0–100 cm) (Guo et al, 2016). In addition, a recent study (Shi, Wang, Xu, Zhang, & Luo, 2017) has showed that SOC level is significantly lower in subsoil in the upper YRD than in the Hebei Plain with the same soil type and cropping system, and their analysis suggests that the lower levels of SOC in the YRD may be partly resulted from hydrological processes (e.g., salty water movements) that could lead to desorption of SOC and subsequently leaching/removal of DOC. In this study, we selected three sections in typical croplands (with various degrees of salinity) in the YRD, and evaluated the variability of SOC, SIC, and water‐extractable organic carbon (WEOC) together with other soil properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that in the YRD, SOC stock is generally lower in the higher salinity soils (3.05 kg C m −2 in the 0–60 cm) (Setia et al, 2013) than in the lower salinity soils (5.73 kg C m −2 in the 0–100 cm) (Guo et al, 2016). In addition, a recent study (Shi, Wang, Xu, Zhang, & Luo, 2017) has showed that SOC level is significantly lower in subsoil in the upper YRD than in the Hebei Plain with the same soil type and cropping system, and their analysis suggests that the lower levels of SOC in the YRD may be partly resulted from hydrological processes (e.g., salty water movements) that could lead to desorption of SOC and subsequently leaching/removal of DOC. In this study, we selected three sections in typical croplands (with various degrees of salinity) in the YRD, and evaluated the variability of SOC, SIC, and water‐extractable organic carbon (WEOC) together with other soil properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, our approach could introduce bias or uncertainty due to the choice of end member value for soil C:N ratio. According to our recent study 31 , soil C:N ratio varied from 9.5 to 13.4 in the middle-lower parts of Yellow River Basin. If we chose 9.5 (or 13.4) as the soil C:N end member, the terrigenous contribution would be increased (or decreased) by 4–25%.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, the C/N ratio was significantly positively correlated with SOC following vegetation restoration, including farmland. Deng et al [55] and Shi et al [25] also found that a low soil C/N ratio was associated with low SOC in the cropping system of the North China Plain. [56][57][58].…”
Section: Depthwise Distribution Of Soil Organic Carbonmentioning
confidence: 96%